(untitled) (Annals of Medical Research, 2022)
Aim: Service life of a maxillofacial prosthesis is too short especially because of color instability. This study aimed to investigate the effects of hand soap and chlorhexidine gluconate mouthwash on the color of maxillofacial prosthesis after exposure of cigarette smoke. Materials and Methods: Sixty specimens were fabricated from a maxillofacial silicone material. Two groups (n=20) were pigmented intrinsically mimicking dark and fair tone skin and one group was not pigmented for control. All the specimens were exposed to cigarette smoke in a closed apparatus designed for the study. Color measurements of the specimens were performed before and after smoke exposition by using a spectrophotometer. Half of all the specimens (n=30) consisting of dark, fair and non-pigmented ones was rubbed with liquid hand soap and the other half was immersed in chlorhexidine gluconate mouthwash (0.12% chlorhexidine digluconate). Color measurement was repeated after cleaning process. Color differences were calculated both CIELab (ΔE*ab) and CIEDE2000 (ΔE00) color measurement formulas. Results: Color groups had significantly different color change values in terms of ΔE00 and ΔE*ab after exposition to smoke and cleaning methods (p<0.001). The effect of soap and chlorhexidine on color change values did not differ from each other (p=0.284 for ΔE00, p=0.312 for ΔE*ab). The interaction of color groups with cleaning methods was statistically insignificant (p=0.962 for ΔE00, p=0.550 for ΔE*ab). ΔE00 and ΔE*ab values showing color alteration between initial color and after cleaning were significantly different in groups (p<0.001). Conclusion: Cleaning process using hand soap and chlorhexidine gluconate mouthwash succeed to return the color of stained silicone to the initial color.